2019
DOI: 10.1136/rapm-2019-100651
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperalgesia effect of AMP-activated protein kinase (AMPK) activators in a mouse model of postoperative pain

Abstract: Background and objectivesAMP-activated protein kinase (AMPK) activator drugs decrease hypersensitivity in mice with pain. This study examines if postsurgery treatment with the prototype AMPK activator metformin and a new mechanism-specific AMPK activator, O304, after plantar hindpaw incision in mice, would reduce mechanical hypersensitivity and produce changes in the AMPK pathway in the dorsal root ganglion (DRG).MethodsTo create postoperative pain, an incision was made in the left plantar hindpaw. Animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…10,11 Mouse model studies have demonstrated that AMPK activation can reduce peripheral nerve injury and allodynia within 7 days of injury. 12 AMPK activators have also demonstrated complete resolution of long-standing nerve injury within 60 days of the event. One study looked at metformin and O304 in a postoperative pain mouse model and demonstrated reduced mechanical pain sensitivity with both agents compared with the drug vehicle.…”
Section: Ampk Activatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Mouse model studies have demonstrated that AMPK activation can reduce peripheral nerve injury and allodynia within 7 days of injury. 12 AMPK activators have also demonstrated complete resolution of long-standing nerve injury within 60 days of the event. One study looked at metformin and O304 in a postoperative pain mouse model and demonstrated reduced mechanical pain sensitivity with both agents compared with the drug vehicle.…”
Section: Ampk Activatorsmentioning
confidence: 99%
“…This study also demonstrated an even greater synergistic effect with both agents co-administered. 12 There are rich opportunities for further study and expansion within this field. Metformin studies may be designed to evaluate treatment of postsurgical and neuropathic pain, possibly as part of a preemptive perioperative regimen such as an enhanced recovery after surgery protocol.…”
Section: Ampk Activatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest your excellent paper on the antihyperalgesic effect of AMP-activated protein kinase (AMPK) activators 1. The fact that you assert that the value of the drug may be in the postsurgical period in patients with diabetic neuropathy caught our attention.…”
mentioning
confidence: 99%
“…The goal of our published paper ‘Antihyperalgesia effect of AMP-activated protein kinase (AMPK) activators in a mouse model of postoperative pain’ was to find the analgesic efficacy of AMP-activated protein kinase activators in a postsurgical pain model and to evaluate the metabolic pathways by which AMPK activator drugs can modulate nociception 1. This might allow the reduction or elimination of opioids for postsurgical pain, a goal that anesthesiologists are striving for.…”
mentioning
confidence: 99%